2008
DOI: 10.1038/nature06888
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide screen reveals APC-associated RNAs enriched in cell protrusions

Abstract: RNA localization is important for establishment and maintenance of polarity in multiple cell types. Localized RNAs are usually transported along microtubules or actin filaments 1 , and become anchored at their destination to some underlying subcellular structure. Retention commonly involves actin or actin-associated proteins 2-7 , although cytokeratin filaments and dynein anchor certain RNAs 8,9 . RNA polarization is important for diverse processes ranging from cell fate determination to synaptic plasticity. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
347
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(370 citation statements)
references
References 32 publications
21
347
0
2
Order By: Relevance
“…6A): transcripts, which become translated at the endoplasmic reticulum (ER), should have a shorter distance to the nucleus compared to transcripts with a cytoplasmic translation. For instance, we noticed that transcripts of RAB13, which have previously been described to enrich in filopodia [35], tended to be furthest from the nucleus (Fig. 6B).…”
Section: Quantification Of Spot Localizationmentioning
confidence: 64%
“…6A): transcripts, which become translated at the endoplasmic reticulum (ER), should have a shorter distance to the nucleus compared to transcripts with a cytoplasmic translation. For instance, we noticed that transcripts of RAB13, which have previously been described to enrich in filopodia [35], tended to be furthest from the nucleus (Fig. 6B).…”
Section: Quantification Of Spot Localizationmentioning
confidence: 64%
“…3;Jansen, 2001;Czaplinski and Singer, 2006;Bramham and Wells, 2007;Singer, 2008). Recent genome-wide screen of RNAs localized in leading edge of migrating mammalian fibroblasts showed that in response to migratory stimuli, 50 different mRNAs (besides previously identified b-actin mRNA) accumulated, via microtubule mediated transport, in the fibroblast protrusions rich in actin cytoskeletal elements (Mili et al, 2008). In epithelial cells, the apical cytoskeleton containing cytokeratin, actin, and microtubules (Salas et al, 1997;Sugimoto et al, 2008) is enriched in localized wingless mRNA (Simmonds et al, 2001;Najand and Simmonds, 2007).…”
Section: Structural Role Of Rna In the Cytoplasm Organization And Maimentioning
confidence: 98%
“…More than 70% of mRNAs of 3370 genes analyzed were asymmetrically expressed in Drosophila [52]. The first systematic investigation of mRNA localization in mammalian cells found that more than 50 species of mRNA preferentially accumulate in the cellular protrusions of migrating mouse NIH3T3 fibroblasts [53].…”
Section: Cellular Infrastructure: Localized Protein Expression and DImentioning
confidence: 99%